The effect of compression garments on performance in elite winter biathletes (International Journal of Sports Physiology and Performance, 2021)
Purpose: To evaluate the effects of wearing upper- and lower-body compression garments on cross-country skiing performance in elite winter biathletes. Methods: A total of 7 senior biathletes (4 men and 3 women) from the Swedish national team performed 2 exercise trials in a randomized and counterbalanced order, wearing either commercially available upper- and lower-body compression garments (COMP) or a standard winter-biathlon racing suit (CON). In each trial, the athletes roller-skied on a customized treadmill, completing a time trial simulating the skiing duration of a biathlon sprint race, followed by a time-to-exhaustion test designed to elicit exhaustion within ~60 to 90 seconds. Heart rate, blood lactate concentration, rating of perceived exertion, thermal sensation, and thermal comfort were monitored throughout each trial, while muscle soreness was measured up to 48 hours after each trial. Results: Pressure exerted by the clothing was significantly higher at all anatomical sites for COMP compared with CON (P = .002). Wearing COMP led to small positive effects on time-trial (d = 0.31) and time-to-exhaustion test (d = 0.31) performances compared with CON, but these differences were not statistically significant (P > .05). No significant differences were found for any physiological (heart rate or blood lactate concentration) or subjective (rating of perceived exertion, thermal sensation, thermal comfort, or muscle soreness) responses between COMP and CON (P > .05). Conclusion: Wearing COMP during maximal cross-country skiing may have small but worthwhile beneficial effects on performance for some individuals. Due to individual variation, athletes are advised to test COMP prior to competition.